Simulation of muon radiography for monitoring CO2 stored in a geological reservoir. (November 2015) - Klinger, J.; Clark, S.J.; Coleman, M.; Gluyas, J.G.; Kudryavtsev, V.A.; Lincoln, D.L.; Pal, S.; Paling, S.M.; Spooner, N.J.C.; Telfer, S.; Thompson, L.F.; Woodward, D.
Abstract : Highlights: First detailed simulation of muon radiography with application for carbon capture and storage monitoring. Includes a detailed model of geological stratigraphy. Includes a detailed model of fluid dynamics to describe the subsurface CO2 distribution. We show that muon radiography is sensitive to changes in the overburden density of less than 1%. We show that 50 days is sufficient to observe such changes in the overburden density distributions. Abstract: Current methods of monitoring subsurface CO2, such as repeat seismic surveys, are episodic and require highly skilled personnel to acquire the data. Simulations based on simplified models have previously shown that muon radiography could be automated to continuously monitor CO2 injection and migration, in addition to reducing the overall cost of monitoring. In this paper, we present a simulation of the monitoring of CO2 plume evolution in a geological reservoir using muon radiography. The stratigraphy in the vicinity of a nominal test facility is modelled using geological data, and a numerical fluid flow model is used to describe the time evolution of the CO2 plume. A planar detection region with a surface area of 1000 m 2 is considered, at a vertical depth of 776 m below the seabed. We find that 1 year of constant CO2 injection leads to changes in the column density of ≲1%, and that the CO2 plume is already resolvable with an exposure time of less than 50 days.